Diskursus Moderasi Dusun Tiga Agama, Buneng: Implementasi Pendidikan Multikultural Siswa SMP - Moh. Badrus Solichin (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2020)
The harmony of the people of Buneng Hamlet who believe in three different religions is the main attraction of this research. How the Buneng community has lived for decades with religious differences, but these differences can actually be interpreted by society as a form of diversity. Then the religious harmony found is used as material in multicultural education learning for junior high school students. This issue is the focus of this research problem. The research method uses field research, namely data collected based on observations in the field. The results of this study indicate: first, the harmony in the religious tolerance of the people of Dusun Buneng was born from customs/traditions which are inherited from their ancestors; second, the people of Dusun Buneng who live in harmony, help between religions, are tolerant and open to each other in opinions and attitudes, which is a reflection of religious moderation; third, the implementation of multicultural education through the values of harmonization and tolerance which is reflected in the life of the Buneng community for junior high school students.